Penanganan Depresi Pada Lanjut Usia Di Panti Griya Sehat Bahagia Karanganyar - Ratri, Prapti Madyo; , Santi Sulandari, S.Psi.,M.Ger (2016)
Elderly are a group indidvidu over the age of 60 years and is the final stage of development followed by some gradual changes. Changes experienced when stepping elderly cause some disruption, one of which is depression. Elderly depressed majority are elderly people who live in institutions, but in this phenomenon is happening shows that the elderly who live in homes more comfortable and happy than to live with his family. This study aims to determine treatment for depression in the elderly in Panti Griya Sehat Bahagia Karanganyar. This study used a qualitative approach to data collection using semi-structured interview technique and observation techniques. Informants in this study were selected by purposive sampling amounted to 4 informants a doctor at the Panti Griya Sehat Bahagia Karanganyar and 3 nurse or clerk at the Panti Griya Sehat Bahagia Karanganyar. As for the supporters informant came from elderly patients aged 60 years and depressed living in Panti Griya Sehat Bahagia Karanganyar. Data was analyzed thematically appropriate themes that are needed in research. The results of this study indicate that there are five types of treatment provided by the institutions in suppressing levels of depression experienced by the elderly, such as self-talk, sedatives, the intensity of nurse communication with patients, physical therapy, and closeness to God. Self Talk therapy is given to patients with hallucinations to reject a whisper. Sedative pills for patients with low and moderate depression, while the drip type drugs for patients with major depression. The intensity of nurse communication with patients given a way to invite the patient to tell a story. Physical therapy in the form of an invitation to move your body, head, hands for 10 seconds. Closeness to God was given to the provision of training praying and reading the Quran to Islamic religious patients and their reflections and meetings of pastors every Friday and Sunday for patients who are Christians.